CONCEPTUAL METAPHOR IN FOOTBALL NEWS ON GOAL.COM - Surahman, Fauzi Akbar; Rosalinah, Yanti; Alhaq, Muhammad Wafdan (JOURNAL OF LANGUAGE, 2024)
This research examines conceptual metaphors as defined by Lakoff and Johnson, focusing on three types: structural, ontological, and orientational. The study analyzes an editorial from Goal.com titled, "Arsenal have no margin for error! Gunners told Liverpool showdown is 'must-win' in title race just eight games into 2024-25 season," using a qualitative approach grounded in cognitive semantic theory to explore the nuanced meanings conveyed through metaphor in sports commentary. Known for its in-depth and timely football analysis, Goal.com offers insights into how metaphors enhance fans' understanding of competitive sports narratives. Data collection involved close reading and note-taking, identifying instances of structural, ontological, and orientational metaphors, along with their source and target domains and image schemas. Findings reveal five structural metaphors, which use schemas such as Scale and Force to emphasize competitive intensity; four ontological metaphors, drawing on Container, Force, and Existence schemas to illustrate team pressures; and one orientational metaphor, using the Container schema to deepen spatial and relational context in the text. This study highlights the role of sports media metaphors in shaping public perception, making abstract concepts like competition and resilience more tangible. By framing sports challenges in relatable, high-stakes terms, these metaphors foster emotional engagement among fans, creating a shared understanding of a team's journey and pressures and underscoring the powerful influence of metaphor in sports narratives.